Species diversity and distribution of genus Pampus (Pelagiaria: Stromateidae) based on global mitochondrial data - Wei, Jiehong; Wu, Renxie; Jawad, Laith A.; Xiao, Yongshuang; Loh, Kar-Hoe; Herrera-Ulloa, Angel; Wang, Yajun; Liu, Jing; Xu, Kuidong (Frontiers in Marine Science, 2022)
Due to the highly similar external morphology of the Pampus species, misidentifications frequently occur and hinder the understanding of the taxonomy and species distributions of the genus. In this study, we generated 271 mitochondrial sequences and obtained 1,226 sequences from the public databases to understand the species diversity and distributions of the genus Pampus. Most phylogenetic analyses and species delimitations congruently concluded seven valid species within the genus Pampus (i.e., P. argenteus, P. candidus, P. chinensis, P. cinereus, P. liuorum, P. minor, and P. punctatissimus). Sequences of P. argenteus are reported through the northern South China Sea to the Japan Archipelago, which covered the type locality of P. echinogaster. Sequences of P. echinogaster in the public databases are all identified as P. argenteus, suggesting that the species should be synonymized with P. argenteus. Furthermore, sequences of P. griseus were identical to our P. cinereus data and, therefore, should be treated as a synonym of the latter. Inference on divergence time and ancestral distribution implied that the genus Pampus originated in the central Indo-Pacific region around 8.35–11.33 million years ago (the late Miocene), associated with the rise of the Indonesian–Australian Archipelago biodiversity hotspot. The divergence between P. cinereus and P. liuorum dated back to 1.20–1.72 million years ago, which might be related to glacial isolation during the Mid-Pleistocene transition.